Startle reaction evoked by kinematic stimuli. Issue 3 (March 2016) - Castellote, J.M.; Kofler, M.; Mayr, A.; Saltuari, L.
Abstract : Background: Kinematic stimuli are used for both assessment and treatment in neurorehabilitation. A patient's voluntary or reflex response may be affected by a startle reaction. We therefore explored whether certain kinematic stimuli are able to elicit a startle reaction. Methods: Eleven healthy subjects were suspended in a Lokomat system and were exposed to unexpected passive left knee flexion at 3 velocities (6, 60, 240°/s). Subjects were asked to perform a right wrist extension as soon as they felt their leg move (conditions: 6-React, 60-React, 240-React, respectively). In some 240°/s trials movement onset was preceded by a low-intensity electrical pre-pulse to the left index finger (240-Prep-React). We recorded EMG activity from right orbicularis oculi and sternocleidomastoid muscles to assess startle responses, from left quadriceps muscle to obtain stretch reflexes, and from right wrist extensors to assess reaction time. Results: Startle responses were present in most 240-Reacttrials, as evidenced by (1) EMG activity in orbicularis oculi and/or sternocleidomastoid, (2) significant reaction time shortening in wrist extensors, and (3) stretch reflex latency shortening in quadriceps, as compared to responses without startle reaction. Only few trials at lower angular velocities resulted in startle responses. In 240-Prep-React trials no startle responses occurred. Conclusions: Kinematic stimuli of high angular velocity, used to assess muscle stiffness, may elicit a generalized startle reaction, which in turn may modulate stretch reflex latencies of the muscle tested in a passive movement paradigm.